2013
DOI: 10.1016/j.ijid.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal humidity may influence Pseudomonas aeruginosa hospital-acquired infection rates

Abstract: Climatic conditions are another factor that may interfere with the IR of Pseudomonas aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Urinary tract infections were associated with higher precipitation (p = 0.04) and temperature (p = 0.02), while hospital-acquired pneumonia was associated with humidity (p = 0.03) and precipitation (p = 0.03). 31 It is unclear why the rate of SSI in our network due to S. aureus increased in the summer but the rate of SSI due to gram-negative rods did not.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Urinary tract infections were associated with higher precipitation (p = 0.04) and temperature (p = 0.02), while hospital-acquired pneumonia was associated with humidity (p = 0.03) and precipitation (p = 0.03). 31 It is unclear why the rate of SSI in our network due to S. aureus increased in the summer but the rate of SSI due to gram-negative rods did not.…”
Section: Discussionmentioning
confidence: 81%
“…For example, infections caused by gram-negative bacteria such as Escherichia coli, Acinetobacter baumanii, Pseudomonas aureginosa , and Enterobacter cloacae occur more frequently in warmer summer and fall months than the remainder of the year. 13,24,29,31,33 Similarly, skin and soft-tissue infections caused by Staphylococcus aureus occur more frequently in the summer, 9,24,36 while pneumonia due to methicillin-resistant S. aureus (MRSA) may occur more frequently in the winter. 16,19,35 …”
mentioning
confidence: 99%
“…These results were consistent with (Kaur and Wankhede, 2013). They were found that 65% of the isolates resistant to antibio-tics have the ability to form the biofilm, unlike the isolates that cannot form This biofilm indicates the importance of the biofilm and its role in the emergence of highly antibiotics resistance by many of bacterial species that produce it (Bacalso et al, 2011) that help it to adhere to host cells (Vallet et al, 2004) and gave it the protection of bacteria from external conditions is not appropriate, which helps to stay on hard surfaces, especially in the hospital environment and this leads to the occurrence of injuries acquired from hospitals (Nosocomial infections) (Ramos et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Few studies determined the relationship of increasing temperature and humidity with the nosocomial urinary tract infection caused by Pseudomonas aeruginosa. Some other studies linked urinary tract infections with high temperature and low humidity (17,18,19). The relationship between humidity and urinary tract infection needs to be further investigated before reaching any definite conclusions.…”
Section: Relationship Between Environmental Conditions and Nosocomialmentioning
confidence: 99%